Homer's traditional art. - Foley, John Miles (Pennsylvania State University Press, 1999)
In recent decades, the evidence for an oral epic tradition in ancient Greece has grown enormously along with our ever-increasing awareness of worldwide oral traditions. John Foley here examines the artistic implications that oral tradition holds for the understanding of the Iliad and Odyssey in order to establish a context for their original performance and modern-day reception. In Homer's Traditional Art, Foley addresses three crucially interlocking areas that lead us to a fuller appreciation of the Homeric poems. He first explores the reality of Homer as their actual author, examining historical and comparative evidence to propose that "Homer" is a legendary and anthropomorphic figure rather than a real-life author. He next presents the poetic tradition as a specialized and highly resonant language bristling with idiomatic implication. Finally, he looks at Homer's overall artistic achievement, showing that it is best evaluated via a poetics aimed specifically at works that emerge from oral tradition. Along the way, Foley offers new perspectives on such topics as characterization and personal interaction in the epics, the nature of Penelope's heroism, the implications of feasting and lament, and the problematic ending of the Odyssey. His comparative references to the South Slavic oral epic open up new vistas on Homer's language, narrative patterning, and identity. Homer's Traditional Art represents a disentangling of the interwoven strands of orality, textuality, and verbal art. It shows how we can learn to appreciate how Homer's art succeeds not in spite of the oral tradition in which it was composed but rather through its unique agency.